HUBUNGAN DURASI PENGGUNAAN GAWAI, TINGKAT STRES, JENIS KELAMIN, DAN TEMPAT TINGGAL DENGAN POLA MAKAN REMAJA DI JEMBER - Rohim, Wardasaidah Alfain (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Changes in dietary habits and lifestyles in adolescents are due to rapid growth and development. This study aims to determine the factors correlated with dietary habits of adolescents at MAN 1 Jember. This study is a quantitative study with a cross sectional approach. 273 samples from classes X and XI were obtained based on simple random sampling method. The instruments that were used were Screen Time Questionnare, Despression on Anxiety Stress Scale (DASS) questionnaire, food record and Individual Dietary Diversity Score (IDDS) which were valid and reliable. Correlations were analyzed using Spearman Rank test, while differences were analyzed using Chi Square test. The results showed that there was a correlation between duration of gadget use with energy intake (p=0,002), food diversity (p=0,031), and meal frequency (p=0,001). There was a correlation between stress level with energy intake (p=0,048), food diversity (p=0,014), and meal frequency (p=0,001). There was a correlation between gender with energy intake (p=0,000), food diversity (p=0,001), and meal frequency (p=0,007). There was no correlation between living place with energy intake (p=0,600), food diversity (p=0,853), and meal frequency (p=0,808). Keyword: gadget, stress level, gender, living place, dietary habit